2020
DOI: 10.20448/journal.509.2020.71.22.27
|View full text |Cite
|
Sign up to set email alerts
|

Textbook Evaluation of a General English Textbook for Senior Foreign Language Learners: Application of a Textbook Evaluation Checklist

Abstract: English language learning is one of the most famous and popular learning destinations and interests for many adults and returning students in the East Asian region, particularly for senior citizens who want to expand their horizon during late adulthood. Although there are many foreign language learning schools, self-learning books, video-oriented materials, and even social media channels for students who want to study an additional language during their leisure time, locating a useful and appropriate textbook … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In the case of South Korea, although the government did not officially indicate colleges and universities graduates must have certain levels of the English language proficiency in order to earn their undergraduate degree, many colleges and universities required students to take different types of English language examinations and tests before graduation [5]. However, locating the appropriate textbooks and related materials, such as videos, audio-recording, exercises, and even teachers' teaching materials, is the most important process as both teachers and students rely on the applications and instructions [11][12][13][14][15]. As a result, there are four purposes for this study.…”
Section: The Purpose and Significance Of The Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of South Korea, although the government did not officially indicate colleges and universities graduates must have certain levels of the English language proficiency in order to earn their undergraduate degree, many colleges and universities required students to take different types of English language examinations and tests before graduation [5]. However, locating the appropriate textbooks and related materials, such as videos, audio-recording, exercises, and even teachers' teaching materials, is the most important process as both teachers and students rely on the applications and instructions [11][12][13][14][15]. As a result, there are four purposes for this study.…”
Section: The Purpose and Significance Of The Researchmentioning
confidence: 99%
“…Most textbooks and materials may be evaluated with the checklists and evaluation forms, regardless of the subject matters. For example, several previous studies had employed the checklists to understand the appropriateness and effectiveness of foreign language textbooks internationally [11,13,15,27,28]. These studies employed the checklist as the tool to evaluate the appropriateness and applications of the textbooks and related materials from the perspectives of students, teachers, department heads and school leaders with the connection of the industry leaders.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…We More importantly, many students indicated that the videos always encouraged their interests of learning about nursing education and the potential of joining the nursing profession during the first year of their university voyage [43]. Although many did not have experience in any hospitals or clinics, the videos increased their understanding within the classroom environment, saying, …of course the videos increased our interests…totally increased and motivated…all of us could experience the busy and updated situation in our local public health centres and clinics in our community…so we met our potential supervisors and staff in the videos…it is very motivated and positive… (Student #32, Focus Group) …we are not prepared to go to the hospital or clinics for visiting as we are only first year students…if we go there, we may interrupt the medical professionals…but some real-life videos from our communities…some useful medicines, including some oriental herbs…always allow us to understand the overall background, and perhaps the expectations…being a nurse in the future (Student #40, Interview Session)…”
Section: Application Of the Videosmentioning
confidence: 99%